A national pharmacoepidemiological study of antibiotic use in Korean paediatric outpatients. Issue 7 (24th January 2017) - Song, Yun-Kyoung; Han, Nayoung; Kim, Myeong Gyu; Chang, Hyeu-jin; Sohn, Hyun Soon; Ji, Eunhee; Oh, Jung Mi
Abstract : Background: Information on the use of antibiotics in Eastern Asian children is limited. The objectives of this study were to evaluate in Korean paediatric outpatients (1) the nationwide pattern of prescribing antibiotics according to age group and medical institution and (2) the adherence of antibiotic use for acute respiratory tract infections to both national guidelines and European antibiotic prescribing quality indicators. Method: This population-based study used the national insurance reimbursement database for 2011. The study subjects were outpatients younger than 18 years old prescribed systemic antibiotics. Patterns of antibiotic prescription were compared according to diagnostic conditions, age group and medical institution. The disease-specific proportion of recommended antibiotic or quinolone use for acute respiratory tract infections was evaluated on the basis of clinical practice guidelines and European quality indicators. Results: The data consisted of 70.7 million prescription records for 7.9 million paediatric outpatients, which means that 79.3% of the whole paediatric population used antibiotics. Broad-spectrum antibiotics made up 78.5% of the prescriptions, with broad-spectrum penicillins such as amoxicillin/clavulanate being the most commonly prescribed (50.2%). They were prescribed more commonly in younger paediatric patients (∼80%) than in adolescents (66.6%). The leading diagnosis accounting for antibiotic prescription was bronchitis (35.9%). The prescription proportion of recommended antibiotics in the European quality indicators was extremely low compared with the national guidelines: <0.1% for pharyngotonsillitis and 13.4% for acute otitis media. Conclusions: Antibiotic use in children in Korea is inappropriately high. In addition, broad-spectrum antibiotics are used excessively.